Livelihood strategies in endemic livestock production systems in sub-humid zone of West Africa: Trends, tradeoffs and implications - Zaibet, L.; Traoré, S.; Ayantunde, Augustine A.; Marshall, Karen; Johnson, Nancy L.; Siegmund-Schultze, M. (Springer, 2011)
Rural livelihoods in West Africa depend largely on livestock. The sub-humid and humid zones of the region, however, are highly affected by the tsetse flies, vector of trypanosomosis, by severely limiting livestock production and livelihood options. Endemic ruminant livestock breeds are trypanotolerant, but perceived as inferior compared to other breeds in terms of productivity. The paper shows trends of relative decline in endemic population as a result of increased crossbreeding, largely with zebu cattle and Sahelian sheep and goats, and considerable decline in habitat quality due to forest conversion, logging activities and bushfires. The trade-offs between livelihoods and income strategies and endemic ruminant and habitat conservation are captured by an understanding of the socio-economic conditions and potential drivers of breed choices and forest use within households and communities. The paper shows that livelihood analysis is an important step in understanding impacts and therefore responses to development projects and to ensure that the poorest categories are not excluded from development interventions.